Sexually Transmitted Infection Trends Among Gay or Bisexual Men From a Clinic-Based Sentinel Surveillance System in British Columbia, Canada. Issue 3 (March 2015) - Ling, Daphne I.; Janjua, Naveed Z.; Wong, Stanley; Krajden, Mel; Hoang, Linda; Morshed, Muhammad; Achen, Melanie; Murti, Michelle; Lester, Richard T.; Wong, Jason; Ogilvie, Gina; Gilbert, Mark
Abstract : Introduction: We described trends for sexually transmitted infections (STI) among gay/bisexual men in British Columbia, Canada, using a sentinel site surveillance approach. Methods: Using data from an electronic charting system, we included gay/bisexual men who visited high-volume STI clinics from 2000 to 2013. Diagnosis rates and incidence density were calculated for chlamydia, gonorrhea, syphilis, HIV, hepatitis C, genital herpes, and genital warts. Incidence density was estimated among repeat testers who converted from a negative to positive test result. We also conducted Poisson regression analysis to determine factors that were associated with increased incidence rates. Results: A total of 47, 170 visits were identified for gay/bisexual men during our time frame. The median age was 34 years (interquartile range, 27–43 years), and most clients were seen in Vancouver. Although trends for most STI were stable, diagnoses of gonorrhea and syphilis have risen steadily in recent years. Coinfection with HIV was associated with higher gonorrhea and syphilis rates in the Poisson regression model. In addition, visiting a Vancouver clinic and younger age were associated with increased incidence. Conclusions: Our clinic-based sentinel surveillance system found increasing trends for gonorrhea and syphilis among gay/bisexual men but not for other STI in British Columbia. Further investigation is required to explore the syndemic effects of syphilis, gonorrhea, and HIV. This new platform will be a valuable tool for ongoing monitoring of STI and targeting prevention efforts. Abstract : A sentinel surveillance system was developed using sexually transmitted infection clinic data to describe trends for sexually transmitted infection among gay/bisexual men in British Columbia, Canada. Supplemental Digital Content is available in the article.